DISPARITAS PUTUSAN HAKIM DALAM TINDAK PIDANA MUTILASI TERHADAP ANAK (STUDI KASUS PUTUSAN PENGADILAN NEGERI SIAK NOMOR 05/PIDSUS.ANAK/2014/PN.SIAK DAN PUTUSAN PENGADILAN TINGGI PEKANBARU NOMOR 01/PIDSUS ANAK/2014/PT/PBR - Tampubolon, Andreas Cassiga; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Since human beings are born into the world in need of food, clothing, shelter to pursue his life. In his life, humans are surrounded various kinds of crimes that threaten its interests. The number of crimes that occur can make people restless including mutilation a criminal offense where the victim had been killed, cut his body into pieces and parts of his body were sold to butchers and claimed that the meat sold is animal flesh. The purpose of this study was to determine the basic considerations Siak District Court No. 05 / PIDSUS.ANAK / 2014 / PN.Siak in deciding the case in the Siak mutilation a criminal offense and to know the basic consideration High Court judge Pekanbaru No. 01 / PIDSUS ANAK / 2014 / PT / PBR in deciding criminal cases mutilation in Siak and ideally To find court decisions in criminal cases mutilation in Siak thus Neither the defendant nor the victim get the justice of the law. This study uses normative juridical approach, namely by reviewing legislation, legal theories related to the issues discussed as well as the legal synchronization approach.The data used is secondary data, namely: data support the completeness of the information or support the Primary Data obtained from libraries and library collections author conducted by way of literature or literature. Results of this study is that in deciding the case, a judge should pay attention to things or kaedah seadilnya properly and without any political interests, private interests that could harm either party. In the case of mutilation is a criminal offense, a defendant initials DP who were aged 16 (sixteen) were only asked to wrap the body parts into plastic to be sold and at the time of the defendant's actions in a forced position which inevitably have to perform such actions as it gets which can eliminate the threat of his life. When tried in a state court siak, the defendant was sentenced to ten years in prison by a district court judge siak. It is indeed very unfair to the defendant because of the judge's decision is too heavy especially the accused was 16 years old and the next generation of the family. Therefore, the defendant and the attorney and the public prosecutor to appeal, and in the high court, after notice and look based on facts, evidence and witness testimony in the trial, pekanbaru high court judge acquitted the accused. Therefore capabilities, status and dignity as well as his dignity restored.Keywords: Disparity-Judge Court Decision-Considerations